2019
DOI: 10.1177/2058460119834690
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided pancreas segmentation based on 3D GRE Dixon MRI: a feasibility study

Abstract: Background Pancreas segmentation is of great significance for pancreatic cancer radiotherapy positioning, pancreatic structure, and function evaluation. Purpose To investigate the feasibility of computer-aided pancreas segmentation based on optimized three-dimensional (3D) Dixon magnetic resonance imaging (MRI). Material and Methods Seventeen healthy volunteers (13 men, 4 women; mean age = 53.4 ± 13.2 years; age range = 28–76 years) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Presently, the accuracy of automated pancreas segmentation has lagged behind other abdominal organs 18 , likely due to the pancreas being a small, flexible abdominal organ with a high degree of variation among individuals in both shape and volume. A previous study found that Dice coefficients between computer models of pancreas segmentation and manual segmentation by radiologist were agreeable across the head, body, and tail of the pancreas 19 . Another study demonstrated reproducibility in a hybrid gradient, region growth and shape constraint segmentation method across multiple subjects 20 .…”
Section: Discussionmentioning
confidence: 89%
“…Presently, the accuracy of automated pancreas segmentation has lagged behind other abdominal organs 18 , likely due to the pancreas being a small, flexible abdominal organ with a high degree of variation among individuals in both shape and volume. A previous study found that Dice coefficients between computer models of pancreas segmentation and manual segmentation by radiologist were agreeable across the head, body, and tail of the pancreas 19 . Another study demonstrated reproducibility in a hybrid gradient, region growth and shape constraint segmentation method across multiple subjects 20 .…”
Section: Discussionmentioning
confidence: 89%
“…Our segmentation of organs like duodenum (0.80) and small intestine (0.87) is even much better than their CT-base segmentation (0.75 in duodenum and 0.80 in the small intestine). For the most studied single organ -pancreas, our DSC 0.88 is still on par with recent state-of-the-art deep learning-based segmentation works [35][36][37][38].…”
Section: Discussionmentioning
confidence: 95%
“…For the most studied single organ pancreas, our DSC of 0.88 is still on par with recent stateof-the-art deep learning-based segmentation works. [45][46][47][48] We believe that there is still room to improve in our network, particularly for organs like the small intestine and duodenum. First, to strike a good balance between computational complexity in 2D and richer geometry context in 3D networks, we will explore the hierarchical multiresolution 3D approach.…”
Section: Discussionmentioning
confidence: 99%